ANALISIS ORGANOLOGI ALAT MUSIK GINGGONG PADA SUKU DAYAK BAKATI RARA KABUPATEN BENGKAYANG - Gresni, Gresni; Istiandini, Winda; Silaban, Chiristianly Yery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research motivated by the uniqueness musical instrument and make musical, ginggong. The purpose of this study was to describe the ingredients and methods of making a musical instrument, describing how to play a musical instrument, describing the design of the implementation of a musical instrument. the theory used is music. Method was needed in the form of a qualitative approach to organology. The data sources used were three sources and one validator with observation techniques, interview techniques, documentation techniques. The validity of the data used three types of triangulation. The results of this study were the basic ingredients of the musical instrument Ginggong are palai wood, bamboo tareng, k, bamboo gare, gumang wood, paradis rattan, branch twigs, bamboo pasa, goat skin. The way to play the ginggong musical instrument in a sitting position on the floor of the foot is stretched and the ginggong the musical instrument body while holding down the strings.The results of this implementation design study are expected to help every teacher in educating students in planting character, social values and knowledge of arts and culture owned by the local area to instill a sense of tolerance and responsibility.Keywords: Ginggong, Music and Art, Traditional Musical InstrumentsÂ Â Â